Hubungan Tingkat Pengetahuan Diabetes Melitus Dan Pola Makan Terhadap Upaya Pencegahan Diabetes Melitus Pada Remaja Kelas 11 IPA Di SMAN 21 Kab. Tangerang Tahun 2025 - Yeshi Monica Gultom; Alfika Safitri (Universitas Yatsi Madani, 2025)
Background: Diabetes Mellitus (DM) is a degenerative disease and ranks among the top four non-communicable diseases that continue to rise annually, posing a global health threat (Sun et al, 2022). Objective: This study aims to examine the relationship between the level of knowledge about diabetes mellitus and dietary patterns with effort to prevent diabetes mellitus among 11th grade science students at SMAN 21, Tangerang Regency. Methods: The research employed a descriptive quantitative design with a cross-sectional approach. The sample consisted of 80 students from 11th-grade science classes, selected through purposive sampling. Research instruments included the DKQ-24 questionnaire to assess knowledge, the Food Frequency Questionnaire (FFQ) to evaluate dietary patterns, and a diabetes prevention questionnaire. Data were analyzed using univariate and bivariate methods with the chi-square test. Results: The findings revealed a significant relationship between knowledge level and dietary patterns with diabetes prevention efforts (p<0.001). Conclusion: Students with good knowledge and healthy eating habits tend to be more proactive in preventing diabetes mellitus. Therefore, health education within the school environment plays a crucial role in fostering healthy behaviors from an early age.